Isolation of high-purity and high-stability exosomes from ginseng - Jang, Jinwoo; Jeong, Haewon; Jang, Eunjae; Kim, Eungpil; Yoon, Youngdae; Jang, Sujeong; Jeong, Han-Seong; Jang, Geupil (Frontiers in Plant Science, 2023)
Exosomes are nano-sized extracellular vesicles that regulate cell growth and defense by delivering bioactive cellular constituents. They are a promising material for biomedical and cosmetic utilization, especially in medicinal crops such as ginseng. One main hurdle to their usage is the need for a method to isolate stable exosomes with high purity. In this study, we first tested two methods to isolate exosomes from ginseng: ultracentrifugation, the most widely used method; and the ExoQuick system, a polymer-based exosome precipitation approach. We also designed and tested a third method in which we combined ultracentrifugation and ExoQuick methods. Size distribution analysis revealed that the exosome isolation purity by the ultracentrifugation and ExoQuick methods alone were 34.1% and 59.7%, respectively, while the combination method greatly improved exosome isolation purity (83.3%). Furthermore, we found that the combination method also increases the colloidal stability of isolated ginseng exosomes, and the increase was almost double that of the ultracentrifugation method. Lastly, we showed that the combination method can also be used to isolate high-purity and high-stability exosomes from the model plant Arabidopsis. Overall, our findings indicate that the combination method is suitable to isolate high-purity and high-stability exosomes from plants including ginseng.